In vivo study of alginate hydrogel conglutinating cells to polycaprolactone vascular scaffolds fabricated by electrospinning. Issue 8 (21st September 2016) - Sun, Kwang‐Hsiao; Liu, Zhao; Liu, Chang‐Jian; Yu, Tong; Zhou, Min; Liu, Cheng; Ran, Feng; Pan, Li‐Jia; Zhang, Huan
Abstract: Objective: The aim of this study was to explore an innovative cell‐seeding technology applied on artificial vascular scaffolds. Methods: Scaffolds were fabricated by electrospinning polycaprolactone (PCL) and seeded with rat endothelial progenitor cells differentiated from adipose‐derived stem cells. Then, we modified the PCL scaffolds through the use of alginate hydrogel conglutinating cells (AHCC), a blank alginate hydrogel coating (BAHC), and natural sedimentation seeding cells (NSSC). The blank PCL (BP) scaffolds without any modifications were considered the blank control group. After modification, the scaffolds were implanted in a rat model. The implanted scaffolds were harvested and observed using histological and immunohistochemical methods and scanning electron microscopy (SEM) at 1, 2, and 4 weeks after implantation, respectively. Results: The best regeneration and configuration of the endothelium tissue and the most similar morphology to that of natural endangium was observed qualitatively in the AHCC scaffolds. The BP scaffolds had qualitatively the worst regeneration and configuration and the most dissimilar morphology at the same time point. In the AHCC group, cells could adhere directly on the inner surface of the vascular scaffolds, eliminating the time delay via the NSSC method prior to cell adhesion. Conclusion: AHCC are an effective method for seeding cells on vascular scaffolds and can eliminate the time delay for cell adhesion. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2443–2454, 2017.